Hochfrequenzchirurgie - Prinzipien und Anwendungen = Principals of high frequency surgery - Bergler, Wolfgang; Hörmann, Karl; Hammerschmitt, Nicolas; Huber, Kerstin (Laryngo-Rhino-Otologie, 2004)
Thieme E-Books & E-Journals